2015
DOI: 10.1111/tsq.12086
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Commitment: Looking for Work with a Criminal Record

Abstract: Unemployment is one of the most often cited barriers to reentry, yet we know little about how understandings of work inform the job-search strategies of men and women with felon status. How and why do individuals remain committed to the legitimate labor market and continue their search for employment? We categorized interviews from 38 Milwaukee County residents into four narrative typologies that (1) reflected understandings of work and job market challenges and (2) mapped onto reported job-search strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…While the specific designs of these policies vary across states, they all serve to ban employers from asking job applicants about criminal records until late in the hiring process. By delaying employers' ability to use a job applicant's criminal history as a signal of low employability, BTB policies aim to encourage ex-offenders to apply for positions (Hlavka, Wheelock, and Cossyleon, 2015) and to increase the likelihood that they are selected for a job interview, providing them with an opportunity to mitigate discrimination through face-toface contact and, in turn, improve their employment outcomes (Altonji and Pierret, 2001). One study conducted in Honolulu County found Hawaii's BTB significantly reduced recidivism among ex-felons (D'Alessio, Stolzenberg, and Flexon, 2015), suggesting such policies present large potential benefits.…”
Section: Ban the Boxmentioning
confidence: 99%
“…While the specific designs of these policies vary across states, they all serve to ban employers from asking job applicants about criminal records until late in the hiring process. By delaying employers' ability to use a job applicant's criminal history as a signal of low employability, BTB policies aim to encourage ex-offenders to apply for positions (Hlavka, Wheelock, and Cossyleon, 2015) and to increase the likelihood that they are selected for a job interview, providing them with an opportunity to mitigate discrimination through face-toface contact and, in turn, improve their employment outcomes (Altonji and Pierret, 2001). One study conducted in Honolulu County found Hawaii's BTB significantly reduced recidivism among ex-felons (D'Alessio, Stolzenberg, and Flexon, 2015), suggesting such policies present large potential benefits.…”
Section: Ban the Boxmentioning
confidence: 99%
“…Caught between being discredited and being discreditable (Goffman, 1959), respondents in Maruna's (2001) study developed unique identity management strategies, dependent upon the adaptation of specific cultural scripts. Maruna suggested that explanations of desistance from crime might be strengthened by narrative accounts (also see Harding, 2003;Hlavka et al, 2015;Kaufman & Johnson, 2004;McAdams, 1993). Exoffenders often explain reform as a process of self-transformation and personal decision-making rather than something managed by outside agencies (Maruna et al, 2009).…”
Section: Narratives Of Reentry and Reformmentioning
confidence: 99%
“…In fact, a few interviewees were now employees or volunteers at the nonprofits in this study. Criminal records and prison stints were reframed as credentialing experiences rather than restrictions (also see Hlavka et al, 2015): Jean (female): All of my jobs have been community-based jobs. Most of them has been outreach.…”
Section: Accounts Of Reentry As Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations